Sastra dan sufisme (Studi terhadap Dîwân al-Durr al-Manzhûm li Dzawi al-`Uqûl wa al-Fuhûm karya Syaikh Abdullah al-Haddâd) - Idrus al-Kaf (Tamaddun: Jurnal Kebudayaan dan Sastra Islam, 2019)
Introduction. This article means to reveal some important aspects of the poetry of Syaikh al-Haddâd, and the characteristics of the Dîwân. Data Collection Method. Using a literary approach methode Analysis Data. The data were descriptively analysed by philosophical, and hermeneutical approaches Results and Discussions.The poetry of Syaikh al-Haddâd are the theoretical Sufi poems that are rich in spiritual ideas and experiences. His poetries can be classified into the types of “syi'r al-kasyf wa al-ilham”, it written through the kasyf experience or spiritual vision, because the author has achieved mystical and mystical unity. The author's study to the outer and the inner structure of Dîwân, has strengthened the conclusions that the poetries in dîwân are not a product of reason (logic), but are based more on the “mauhibah Rabbâniyah”, a kind of inpersonal power, and looks very spontaneous and natural. Conclusions. poetry is a medium that is often used by the Sufis to express their Sufism thoughts. because it is through this symbolic and imagery language that the Sufis can give readers the opportunity to improve the "reflection of the beauty of the world" ascending in to "the reflection of divine beauty".". Keyword : literature, sufism, poetry of Syaikh al-Haddâd